2023
DOI: 10.31234/osf.io/teq7k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

50 Years of Anchoring: A Meta-Analysis and Meta-Study of Anchoring Effects

Dan Schley,
Evan Weingarten

Abstract: One of the most robust phenomena studied across the behavioral sciences is numeric anchoring -- where an incidental number preceding a judgment can influence real-world relevant judgments of quantity, price, legal judgments, and more. The authors meta-analyze this expansive literature containing 2,131 total effect sizes (1,050 comparing high anchors against low anchors), finding a large (d = 0.876, 95% CI[0.808, 0.943], I^2 = 92.96%) effect with only a small reduction from publication-bias corrections. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 160 publications
0
1
0
Order By: Relevance
“…Similarly, Berg and Moss (2022) found that participants were influenced by anchors which they had been told to disregard because they were wrong; even though the information to disregard the anchors seemed to at least somewhat decrease their effect. A recent meta-analysis examining moderators of the anchoring effect also found that debiasing interventions on average reduced, but did not eliminate the effect (Schley & Weingarten, 2023). Despite the difficulty of debiasing anchoring effects, here we suggest several potential ways decision makers can reduce anchoring effects (see Table 3 for an overview).…”
Section: Debiasingmentioning
confidence: 42%
“…Similarly, Berg and Moss (2022) found that participants were influenced by anchors which they had been told to disregard because they were wrong; even though the information to disregard the anchors seemed to at least somewhat decrease their effect. A recent meta-analysis examining moderators of the anchoring effect also found that debiasing interventions on average reduced, but did not eliminate the effect (Schley & Weingarten, 2023). Despite the difficulty of debiasing anchoring effects, here we suggest several potential ways decision makers can reduce anchoring effects (see Table 3 for an overview).…”
Section: Debiasingmentioning
confidence: 42%